Avaliação da modulação autonômica e composição corporal em indivíduos com síndrome de down: praticantes ou não de atividade física - CUNHA FILHO, Antonio Silva Andrade (2017)
In the Person with Down Syndrome (DS), autonomic nervous system (ANS) modulation of the heart rhythm can be compromised, resulting in changes in heart rate (HR) and cardiac cycle duration. Capacity to accumulate more adipose tissue is commonly present in people with DS, being this an independent factor for a worse prognosis of sudden death in this population. Objective: To study the effect of physical exercise on autonomic variables and body composition in individuals with active Down Syndrome And sedentary in São Luis-MA. Materials and Methods: This was an analytical and cross-sectional study, data analysis was performed in GraphPad Prism® software, version 5.01 and field research was performed at APAE's in the cities of São Luís - MA. We analyzed 52 individuals with Down Syndrome. Of these individuals, 15 sedentary SD (SDS), 9 SDS (mild active) and 12 SDs (strong active) and 11 controls (CG) were divided through the results obtained in the International Physical Activity Questionnaire (IPAC), anthropometric, hemodynamic and autonomic evaluation in the time domain, frequency domain and symbolic analysis. The constitution in relation to sex was that all were made up of males. Results: SD FH presented lower BMI than Control and SD SD group. Body fat (%) was lower in SED AF / AL than Control and SD group SED. And the hemodynamic parameters were similar between the groups. During the baseline period, there were no significant differences, however, sedentary subjects exhibited lower values in relation to the time domain, such as RR and VAR-RR intervals, when compared to the control group. Frequency domain indexes showed that SD SED individuals had higher values for sympathetic activity regarding low frequency (LF) and similar values for parasympathetic (HF) activity in relation to SD / AF groups. These results, when normalized, presented higher vagal sympathetic balance (LF / HF). In addition, the symbolic analysis showed higher 0V (related to sympathetic activity) and lower values in 2LV (related to parasympathetic activity) in the SD SED group when compared to the control group, SD AL and SD AF. The 2LV was lower in SD-AL and SD AF than in the control group, but 2UV was higher in SD AF than the control group. And there were no differences between the SD / AF group. Conclusion: Thus, we conclude that regardless of intensity, exercise may promote positive adaptations in autonomic modulation in people with Down Syndrome.